Peningkatan Motivasi Dan Hasil Belajar Ipa Pada Materi Sumber Energi Dan Perpindahan Panas Melalui Model Problem Based Learning Di Kelas V MIN 2 Agam - Mulyana, Sri; Supia Wati, Mira (Journal of Development Education and Learning (JODEL), 2025)
This classroom action research was motivated by the low motivation and learning outcomes of fifth-grade students at MIN 2 Agam in the Natural Science subject, particularly on the topic of energy sources and heat transfer. The study aims to improve motivation and learning outcomes through the application of Problem-Based Learning (PBL). The subjects were 23 students. The research was carried out in two cycles. Instruments: learning outcomes test, motivation questionnaire, observation sheet, rubric, and documentation. The results showed an increase in mastery from 30.43% (pretest) to 91.30% (posttest II). High category motivation increased from 26.09% to 82.61%. PBL was effective in improving conceptual understanding and science process skills.